The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep27437
|View full text |Cite
|
Sign up to set email alerts
|

Significance of duon mutations in cancer genomes

Abstract: Functional mutations in coding regions not only affect the structure and function of the protein products, but may also modulate their expression in some cases. This class of mutations, recently dubbed “duon mutations” due to their dual roles, can potentially have major impacts on downstream pathways. However their significance in diseases such as cancer remain unclear. In a survey covering 4606 samples from 19 cancer types, and integrating allelic expression, overall mRNA expression, regulatory motif perturba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…However, the peak in the temperature dependence of specific heat at ∼ 100 K well above T N is characterized by an entropy release of (R/2) ln 2 (R is the gas constant) [12,13], and Raman scattering spectra show fermionic responses [14,15], which have been explained by fractionalized excitations consistent with the Kitaev model. Several experimental studies have found that the application of magnetic field in the honeycome plane can suppress the ZZ order with a critical field of ∼ 7 T [16,17], above which a paramagnetic state appears. Most notably, in a limited field (H) and temperature (T ) range of this field-induced paramagnetic state, the field-dependent thermal Hall conductivity measurements [18][19][20] have revealed a plateau behavior with the value close to one half of quantized thermal Hall conductivity of electronic system.…”
mentioning
confidence: 99%
“…However, the peak in the temperature dependence of specific heat at ∼ 100 K well above T N is characterized by an entropy release of (R/2) ln 2 (R is the gas constant) [12,13], and Raman scattering spectra show fermionic responses [14,15], which have been explained by fractionalized excitations consistent with the Kitaev model. Several experimental studies have found that the application of magnetic field in the honeycome plane can suppress the ZZ order with a critical field of ∼ 7 T [16,17], above which a paramagnetic state appears. Most notably, in a limited field (H) and temperature (T ) range of this field-induced paramagnetic state, the field-dependent thermal Hall conductivity measurements [18][19][20] have revealed a plateau behavior with the value close to one half of quantized thermal Hall conductivity of electronic system.…”
mentioning
confidence: 99%
“…found that at least 14% of coding regions in human genomes can bind transcription factors 50 . The prevalence of such sequences and their implication in diseases suggest their important roles in human genomes and diseases 47 49 , 51 . Third, we compared the conservation score distributions of CDS and UTR indels between cancer genomes and healthy genomes.…”
Section: Discussionmentioning
confidence: 99%
“…About 15% of codons in the human genome were hypersensitive to DNase I treatment, suggesting the existence of likely dual-use sequences for both amino acid coding and transcriptional regulation 50 . These dual function sequences, termed as duons, were considered to be more conserved than non-duon coding sequences and mutations in these duons could lead to diseases 50 , 51 .…”
Section: Introductionmentioning
confidence: 99%
“…Four possible group representations for this exon subregion are suggested in the top of the figure (panel a). These types of protein-coding regions are called duons, since their base-triplets encode information not only for aminoacids but also for transcription enhancers [32][33][34]. Fig.…”
Section: mentioning
confidence: 99%